Penafsiran Term Qawwam pada QS. Al-Nisa’: 34 dan Korelasinya dengan Neurosains - Rifqatul Husna; Ira Bariroh (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Patriarchy is a viewpoint that positions men as superior to women. This perspective is considered legal by many Muslims, using QS. An-Nisa’ verse 34 as its main foundation. This study discusses the word qawwam in that verse to find the correlation between Quraish Shihab's interpretation in Tafsir al-Mishbah and neuroscience, answering whether a husband being qawwam in a household is a privilege that justifies patriarchy and whether, from a neuroscience perspective, he is fit to be a leader. This research is a thematic study using library research methods with data analysis techniques in the form of content analysis. From this research, it can be concluded that, in terms of neuroscience, the responsibility of a man to be qawwam—having an instinct to protect as he is responsible—is a gift directly given by Allah. Men are endowed by Allah with a hypothalamus that is two and a half times larger than that of women. Thus, from a neuroscience perspective, men are more suited to be leaders in the household, which in the Qur’an is referred to as qawwam. However, women are also given advantages by Allah with a corpus callosum that is thicker than that of men. In Tafsir al-Mishbah, the word qawwam is interpreted as a leader and guardian in the sense of fulfilling needs, attention, care, defense, and nurturing. Therefore, the leadership given to the husband is not a privilege but a responsibility that must be carried out properly. The patriarchal culture that views men as superior to women, leading to the neglect of women's rights in the household, is not the leadership desired by the Qur'an and is supported by neuroscience.